Exploring the distinction between Al-generated stories and Human-crafted narratives: A comparative study - Mohammed, Ali (Al-Adab Journal, 2026)
Recently, there has been significant debate about the emergence of AI in creative domains and its impact on storytelling and narrative creation. While some studies suggest that human-authored and AI-generated stories are barely distinguishable, others find that AI-generated stories are poorly structured and often contain repetitive phrases. This study narrows its focus by examining the classic twisty tale The Necklace (1884) by French author Guy de Maupassant, scrutinizing its key features alongside another similar story generated by AI. The AI was provided with six specific prompts to produce a story closely resembling The Necklace and generated a tale titled The Gilded Watch. The two stories are analyzed based on four criteria: narrative structure, character development, language and style, and cultural or historical context.The study finds a significant disparity between AI-generated and human-authored stories, with the former often lacking key storytelling elements. It also suggests that AI’s ability to capture human emotions remains limited.